Effects of Massa Medicata Fermentata on the intestinal pathogenic flagella bacteria and visceral hypersensitivity in rats with irritable bowel syndrome - Zhuang, Zhaomeng; Huang, Chen; Zhang, Yiguang; Lv, Bin (Frontiers in Physiology, 2022)
Objective To investigate the effect of MMF on the changes of pathogenic flagellar bacteria and visceral hypersensitivity(VH) in rats with IBS-D. Methods 30 adult SD rats were randomly divided into normal control group, model control group, and drug intervention group. Acetic acid enema combined with restraint stress was used to build the IBS-D VH model; AWR test was used to assess the visceral sensitivity of rats; 16S RNA was used to analyze the intestinal bacteria, and the content of pathogenic flagellated bacteria were quantitatively counted; The content of flagellin in colonic mucosa was detected by ELISA; TLR5 protein in colonic mucosa of rats was detected by Western Blot. Results After IBS-D modeling, the VH of rats was higher in the model control group than normal control group (p=0.0061 p<0.05), while it was decreased in the drug intervention group (p=0.0217 p<0.05), but without significant difference compared with the normal control group (p=0.6851 p<0.05). The number of fecal Bifidobacterium and Lactobacillus in the model group were decreased compared with the normal control group (p<0.0001); While they were increased in the drug intervention group. The amount of fecal pathogenic flagellated bacteria in the model group was increased compared with the normal control group (p = 0.001 p< 0.05); However it was reduced in the drug intervention group compared with the model group (p = 0.026 p<0.05), which has no statistically difference with the normal control group (p=0.6486 p<0.05). The content of flagellin in colonic mucosa was increased in the model group when compared with the normal control group (p<0.0001), and it was decreased in the drug intervention group (p<0.0001), but there was no statistical difference with the normal control group (p=0.6545 p<0.05). The expression level of TLR5 in colonic mucosa was increased in model control group compared with the normal control group (p=0.0034 p<0.05), However, it was decreased in the drug intervention group(p=0.0019 p< 0.05), but it was no statistical difference with the normal control group (p=0.7519 p<0.05). Conclusion: MMF can reduce VH by decreasing the content of pathogenic flagellated bacteria flagellin and TLR5 protein expression in colonic mucosa in IBS-D rats.